Characteristics of elemental and organic carbon in atmospheric nanoparticles at different sampling locations in Vietnam - Thuy, Nguyen Thi Thu; Dung, Nghiem Trung; Sekiguchi, Kazuhiko; Yamaguchi, Ryosuke; Thuy, Pham Chau; Bang, Ho Quoc (Vietnam Journal of Science and Technology, 2017)
Atmospheric ultrafine particles (NPs or PM0.1) were investigated at a roadside of Nguyen Van Cu road (Vinacomin) and at a mixed site in the Hanoi University of Science and Technology (HUST) in Hanoi, Vietnam. The sampling was conducted during a rainy reason and a dry season to determine the characteristics of atmospheric elemental and organic carbon in the nanoparticles. The relative contributions of organic carbon (OC) and elemental carbon (EC) to total carbon (TC) at HUST were 83.7 – 85.0% and 15.0–16.3 %, respectively; whereas those at Vinacomin’s sampling site accounted for 78.6 – 81.5% and 18.5 – 21.4 %, respectively. The study provides an interesting observation that particulate OC and EC have spatial and temporal variations dependent on sampling sites and weather conditions. In contrast, consistent OC/EC ratios were also found at both seasons of each location, in which the ratios were from 3.68 to 5.68. The correlations of OC and EC were found in the rainy season with the slopes ranging from 0.21–0.34; however, these correlations were not observed in the dry season. The relationships between OC and EC, char – EC and soot – EC can be used in primarily determining the sources of NPs in the atmosphere.